Sistem Deteksi Rem Mendadak dan Tabrakan Pada Motor Menggunakan Sensor Akselerometer Dengan Metode K-Nearest Neighbour Berbasis Arduino - Musada Teguh Andi Afandi; Hurriyatul Fitriyah; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Accident is incident that unpredictable both of victim and witness. But, the accident increased for every years. This is caused by increasing of vehicle unit that ciculate especially motor cycle. When accident happen, family of course doesn't know that an accident has occured to their family who drived the vehicle. So it's needed the system that give the information to the victim family in home. System designed used by many components like arduino mega that used for process datas, accelerometer sensor ADXL345 type for takes datas and GSM SIM900A module as sender of message for victim family. The system uses simple regression as fiture that will be used in K-Nearest Neighbour methode (K-NN) and classification methode K-NN to get incident class. Testing process of system by doing acceleration like brake and crashing and will be classified with K-NN methode so it will get value of accuracy 90% when the tragedy is sudden brake and 60% when accident use K value is 3 for both. While use K valueis 5, a precentage is obtained sytem to get right tragedy is 90% when sudden brake and 50% when accident. So as a whole precentage of system to get right tragedy is 83,33% when use K value 3 and 80% when value is 5.